Visceral Leishmaniasis in China: an Endemic Disease under Control - Lun, Zhao-Rong; Wu, Ming-Shui; Chen, Yun-Fu; Wang, Jun-Yun; Zhou, Xiao-Nong; Liao, Li-Fu; Chen, Jian-Ping; Chow, Larry M. C.; Chang, Kwang Poo (Clinical microbiology reviews, 2015)
Visceral leishmaniasis (VL) caused by Leishmania spp. is an important vector-borne and largely zoonotic disease. In China, three epidemiological types of VL have been described: anthroponotic VL (AVL), mountain-type zoonotic VL (MT-ZVL), and desert-type ZVL (DT-ZVL). These are transmitted by four different sand fly species: Phlebotomus chinensis , P. longiductus , P. wui , and P. alexandri. In 1951, a detailed survey of VL showed that it was rampant in the vast rural areas west, northwest, and north of the Yangtze River. Control programs were designed and implemented stringently by the government at all administrative levels, resulting in elimination of the disease from most areas of endemicity, except the western and northwestern regions. The control programs consisted of (i) diagnosis and chemotherapy of patients, (ii) identification, isolation, and disposal of infected dogs, and (iii) residual insecticide indoor spraying for vector control. The success of the control programs is attributable to massive and effective mobilization of the general public and health workers to the cause. Nationally, the annual incidence is now very low, i.e., only 0.03/100,000 according to the available 2011 official record. The overwhelming majority of cases are reported from sites of endemicity in the western and northwestern regions. Here, we describe in some depth and breadth the current status of epidemiology, diagnosis, treatment, and prevention of the disease, with particular reference to the control programs. Pertinent information has been assembled from scattered literature of the past decades in different languages that are not readily accessible to the scientific community. The information provided constitutes an integral part of our knowledge on leishmaniasis in the global context and will be of special value to those interested in control programs.